Система родини Cyperaceae Juss. флори України - Данилик, І.М. (Український ботанічний журнал, 2012)
Осуществлен анализ современных систем семейства Cyperaceae Juss., которые основаны на молекулярно-филогенетических исследованиях. С использованием новейших данных сис- тематики и обобщения таксономического разнообразия составлена компилятивная систе- ма семейства Cyperaceae флоры Украины. Она включает одно подсемейство, 8 триб, 19 родов и 153 вида. Для каждого таксона приведена номенклатурная цитация. Modern systems of the family Cyperaceae based on molecular phylogenetic research are analysed. Using the most recent information on systematization and generalization of taxonomic diversity, a synoptic system of the family Cyperaceae in the Ukrainian flora is presented. It includes one subfamily, 8 tribes, 19 genera, and 153 species. For each taxon, nomenclatural citation is provided.